The technology of using political discourse as an authentic material for the development of students' critical thinking - Salimova E. T., Amirova O. G. (Socio-Pedagogical Issues of Education and Upbringing, 2021)
The article raises the question of the importance of developing critical thinking in the format of political discourse which has educational and enlightening purposes that contribute students to develop their ability to analyze and critically evaluate what is happening around them. The use of authentic material with the critical thinking development technology is a tool for generating new knowledge.
Keywords: технология развития критического мышления; политический дискурс; critical thinking technology; political discorse in English lessons; урок английского языка